The Effect of Digital Promotion and Perceived Ease of Use on Generation Z Consumptive Behavior in Cirebon, Indonesia - Muhammad Yasser; May Dedu (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The proliferation of digital wallets among Generation Z has intensified scholarly concerns about how promotional exposure and transactional ease shape consumptive spending. This study investigates the effect of digital promotion and perceived ease of use on the consumptive behavior of Generation Z digital wallet users in Cirebon, Indonesia. A quantitative associative design with a cross-sectional survey approach was employed, with data collected from 150 respondents selected through purposive sampling. Eligible participants were Generation Z individuals aged 18–28 years who actively used digital wallet applications in Cirebon. A structured five-point Likert-scale questionnaire was used for data collection, and multiple linear regression was applied for analysis. The results show that digital promotion has a positive and significant partial effect on consumptive behavior (B = 0.664, p < .001), as does perceived ease of use (B = 0.312, p < .001). Both variables simultaneously predict consumptive behavior significantly (F = 319.009, p < .001), jointly explaining 81.3% of its variance (R² = 0.813). Digital promotion emerged as the stronger predictor (β = 0.608), reflecting the behavioral impact of cashback offers, flash sales, and voucher incentives on unplanned and impulsive spending. Perceived ease of use (β = 0.325) further reinforces consumptive tendencies by lowering transactional barriers. Drawing on the Technology Acceptance Model and promotion mix theory, these findings highlight the need for digital financial literacy programs, responsible promotional governance by e-wallet providers, and regulatory attention to the behavioral consequences of digital payment ecosystems. Findings are specific to Generation Z digital wallet users in Cirebon and should not be generalized beyond this context.